2014
DOI: 10.4103/2153-3539.139707
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantification of aligned collagen for human breast carcinoma prognosis

Abstract: Background:Mortality in cancer patients is directly attributable to the ability of cancer cells to metastasize to distant sites from the primary tumor. This migration of tumor cells begins with a remodeling of the local tumor microenvironment, including changes to the extracellular matrix and the recruitment of stromal cells, both of which facilitate invasion of tumor cells into the bloodstream. In breast cancer, it has been proposed that the alignment of collagen fibers surrounding tumor epithelial cells can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
160
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(163 citation statements)
references
References 62 publications
3
160
0
Order By: Relevance
“…This study complements previously reported studies (60–62) by asserting that clinical radiotherapy could be guided and improved by monitoring key cellular processes such as metabolism. Since metabolism plays an important role in cancer invasion and progression (63–65), metabolic profiling may have potential for guiding radiation treatments in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This study complements previously reported studies (60–62) by asserting that clinical radiotherapy could be guided and improved by monitoring key cellular processes such as metabolism. Since metabolism plays an important role in cancer invasion and progression (63–65), metabolic profiling may have potential for guiding radiation treatments in the future.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the in vivo tumor microenvironment, the ECM is classically much stiffer than its innate counterpart. Typically the ECM is aligned in quantifiable organized type I collagen fiber patterns [14,15,129,130]. It also includes increased ECM cross-linking and fiber density [30,106,131-135].…”
Section: Desmoplastic Sdr: Cancer-associated Fibroblasts-ecm Interactmentioning
confidence: 99%
“…For example, using predictors based on the CAF-to-collagen deposition ratio or type I collagen topographical (anisotropic) ECM features, investigators observed a correlation with unfavorable patient survival [76,129,130,136-139]. Others found that actin binding proteins such as palladin, which regulates stromal pro-metastatic CAF and desmoplastic ECM features (e.g., alignment) [140], can be used as a predictive marker of cancer recurrences subsequent to tumor surgical resection [137].…”
Section: Desmoplastic Sdr: Cancer-associated Fibroblasts-ecm Interactmentioning
confidence: 99%
See 1 more Smart Citation
“…Purely synthetic hydrogels, such as polyethylene glycol diacrylate (PEG-DA) scaffolds, can also allow independent manipulation of ligand density and matrix stiffness over a wide range of mechanical properties [29, 30], but, similar to gelatin, lack the ability to recapitulate the fibrous networks of in vivo tissues. This limitation is problematic because fibers may play important roles in directing cell behavior; for example, fibrillar alignment of collagen in breast tumors has been shown to correlate with a worse patient prognosis [31, 32]. The influence of fibrillar structure on cellular outcomes was also highlighted by recent work which described a significant decrease in mouse xenograft tumor growth upon attenuation of fiber formation and crosslinking by inhibition of LOXL2 [33].…”
Section: Introductionmentioning
confidence: 99%